Sustainability index analysis for environmentally low-input integrated farming - E. Widjaja; B.N. Utomo; A.D. Santoso; Y.P. Erlambang; . Surono; M.A. Firmansyah; S. Handoko; E. Erythrina; M.N. Rofiq; D. Iskandar; N.A. Sasongko; T. Rochmadi; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Integrated farming is an efficient and environmentally friendly agricultural activity that uses low-input resources, including abundant local materials, such as waste. According to previous studies, this program has been adopted by the Indonesian government to facilitate the achievement of sustainable agriculture. Therefore, this study aimed to evaluate the level of sustainability of low-input integrated agricultural farming by determining and analyzing the sustainability index.METHODS: Experts and business operators engaged in the integrated production of organic fertilizer, corn, and laying hen farming conducted scientific assessments to gather primary and secondary data. This was carried out through Focus Group Discussions and the completion of a questionnaire containing 34 attributes linked to environmental, economical, social, technological, and institutional aspects. The data obtained were then analyzed using a multidimensional scale technique. Monte Carlo analysis and alternating least-squares algorithm were used to examine sustainability status and significant characteristicsFINDINGS: The degree of agricultural integration's sustainability from organic fertilizer, corn, and layer hen farming was 86.10 percent. The results showed that techniques in several stages of the organic fertilizer production process, corn cultivation with the application of organic fertilizer, and laying hen farming with local feed, harvesting, and marketing, contributed to sustainable development by considering the strength aspects from each dimension. Based on the analysis results, the social dimension had a sustainable index score of 93.79 percent, followed by economic (90.57 percent), institutional (88.39 percent), environmental (83.45 percent), and technology (74.29 percent). Based on the findings, the factors that should be considered included 1) Efficiency in the utilization of water during egg, 2) fertilizer production and effectiveness of using fuel and electricity during the production and marketing, 3) an Industry manager level of education, 4) the ease by which raw materials can be obtained for the integration industry, 5) potential for increasing the low-input integrated agricultural farming, 6) the availability of integration industry facilities, infrastructure and level of expertise needed by managers in the people's integration sector, 7) Financial institutions' existence.CONCLUSION: Multidimensional mapping showed that the low-input integrated agricultural farming in the dry land of Pangkalan Lada District was running sustainably, with an average sustainability index of 86.10 percent. These results indicated that the integration of organic fertilizer, corn, and layer hen farming in the area had successfully optimized the available resources, created a sustainable farming model, and had the potential for adoption in various locations and future periods. The five evaluated dimensions showed good sustainability levels, with sustainability indices ranging from 74.29 percent (sustainable with a fair level) to 93.79 percent (very sustainable). Therefore, sustainability improvements in these farming activities must focus on technological aspects, with an emphasis on technological attributes that offered valuable insights for the government in formulating policies and programs.